Incorporating oral bioaccessibility into human health risk assessment due to potentially toxic elements in extractive waste and contaminated soils from an abandoned mine site. (September 2020) - Mehta, Neha; Cipullo, Sabrina; Cocerva, Tatiana; Coulon, Frederic; Dino, Giovanna Antonella; Ajmone-Marsan, Franco; Padoan, Elio; Cox, Siobhan Fiona; Cave, Mark R.; De Luca, Domenico Antonio
Abstract: The waste rock, tailings and soil around an abandoned mine site in Gorno (northwest Italy) contain elevated concentrations of potentially toxic elements (PTE) exceeding the permissible limits for residential uses. Specifically, the maximum concentrations of As, Cd, Pb, and Zn were 107 mg/kg, 340 mg/kg, 1064 mg/kg, and 148 433 mg/kg, respectively. A site-specific human health risk assessment (HHRA) was conducted for residential and recreational exposure scenarios, using an approach based on Risk Based Corrective Action (RBCA) method, refined by incorporating oral bioaccessibility data. Oral bioaccessibility analyses were performed by simulating the human digestion process in vitro (Unified BARGE Method). Detailed analysis of oral bioaccessible fraction (BAF i.e. ratio of bioaccessible concentrations to total concentrations on <250 μm fraction) indicated BAF of As (5-33%), Cd (72-98%), Co (24-42%), Cr (3-11%), Cu (25-90%), Ni (17-60%), Pb (16-88%) and Zn (73-94%). The solid phase distribution and mineralogical analyses showed that the variation of BAF is attributed to presence of alkaline calcareous rocks and association of PTE with a variety of minerals. The HHRA for ingestion pathway, suggested that bioaccessibility-corrected cancer risk reached up to 2.7 × 10 −5 and 0.55 × 10 −5 for residential and recreational senarios respectively (acceptable level is 1 × 10 −5 ). The hazard index (HI) recalculated after incorporation of oral bioaccessible concentrations for a residential scenario ranged from 0.02 to 17.9. This was above the acceptable level (>1) for 50% of the samples, indicating potential human health risks. This study provides information for site-specific risk assessments and planning future research. Graphical abstract: Image 1 Highlights: As, Cd, Pb and Zn were present in high concentrations at abandoned mine (Gorno). Oral bioaccessibility of potentially toxic elements was highly variable. Calcareous geology, weathering and soil forming process influenced bioaccessibility. Oral bioaccessibility inclusion avoids over-conservative human health risk assessment.